Significant inhibition of photosynthesis and respiration in leaves of Cucumis sativus L. by oxybenzone, an active ingredient in sunscreen. (March 2019) - Zhong, Xin; Li, Yuting; Che, Xingkai; Zhang, Zishan; Li, Yiman; Liu, Binbin; Li, Qingming; Gao, Huiyuan
Abstract: Oxybenzone (OBZ), an active ingredient in most sunscreens, was recently shown to be toxic to humans, corals and other animals. This study is the first to demonstrate that OBZ can significantly inhibit photosynthesis and respiration in the leaves of a higher plant, cucumber. An OBZ suspension content as low as 0.228 mg/L obviously inhibited the photosynthesis and respiration of cucumber. OBZ instantly inhibits the electron transport of chloroplasts and mitochondria in cucumber leaves. Probit analysis demonstrated that the effective content for 20% inhibition of photosynthetic electron transport was 11.7 mg/L (95% confidence level). The inhibition of photosynthesis and respiration restricts carbohydrate synthesis and ATP regeneration, respectively, limiting the energy available for metabolic processes including the synthesis of vital organic macromolecules such as proteins and nucleic acids in plant cells. The inhibition of photosynthesis also enhanced the excess excitation energy in chloroplasts, resulting in overproduction of reactive oxygen species (ROS), and the inhibition of respiration aggravated this process. ROS accumulation adversely affects the structure and function of proteins, DNA and membrane lipids in plant cells, interfering with normal metabolism and even leading to plant death. Therefore, reducing the use of OBZ is important for protecting global ecological security. Graphical abstract: OBZ can enter cells to significantly inhibit photosynthesis and respiration in the leaves of a higher plant, cucumber. OBZ can instantly inhibit the electron transports of chloroplasts and mitochondria. The inhibition of photosynthesis and respiration would restrict the synthesis of carbohydrates and the regeneration of ATP, limiting the energy available for metabolic processes. The inhibition of photosynthesis increased the excess excitation energy in the plant cells, resulting in over-production of reactive oxygen species (ROS), the inhibition of respiration aggravated this process. The over-accumulation of ROS adversely affects the structure and function of proteins, DNA and membrane lipids in plant cells, interfering with normal metabolism and even leading to the death of plant. Image 103 Highlights: The OBZ suspension can instantly inhibit the electron transports of chloroplasts and mitochondria of cucumber. An OBZ suspension content as low as 0.228 mg/L obviously inhibited the photosynthesis and respiration of cucumber. The inhibition of photosynthesis and respiration cause the overproduction of reactive oxygen species (ROS).